Winners and Losers of the Process of Transformation as an Etic Category versus Emic Biographical Perspective - Kaźmierska, Kaja (Qualitative Sociology Review, 2019)
One of the common and schematic descriptions in the perspective of the 1989 breakthrough are two ways of dealing with it by people who are respectively called winners or losers of transformation. These stereotypical characteristics are not only the tool to draw the general image of effects of the transition, but are also based on the specific way of interpretation deeply rooted, for example, in neoliberal thinking. Yet, from the perspective of an individual—so-called Schütz’s man on the street—the categorization of winners and losers not only simplifies the description of social reality, but also it cannot be easily biographically justified because the etic categorization is not always relevant to the emic perspective. In other words, the life history of an individual, showing the main phases and events of biography, and life story—the way that one interprets his/her biographical experiences— may not correspond to each other. The analysis of these two aspects of biography (what is lived through and how it is interpreted) shows how people have dealt with the process of transformation. In the paper, it is presented on the basis of one case study.